Предмет: Математика,
автор: askaelizade145
Докажите тождество : 2аb×(a-b)+(a-b)*(a+b)^2+6ab(b-a)=(a-b)^3
Ответы
Автор ответа:
0
2ab *(a-b)+ (a-b)(a+b)²+6ab(b-a) = (a-b)³
(a-b)*2ab + (a-b)(a+b)² -(a-b)*6ab = (a-b)³
(a-b)(2ab +(a+b)² - 6ab) = (a-b)³
(a-b)(2ab +a²+2ab +b² -6ab) = (a-b)³
(a-b)(a²-2ab +b²) = (a-b)³
(a-b)(a-b)² = (a-b)³
(a-b)³ ≡ (a-b)³
(a-b)*2ab + (a-b)(a+b)² -(a-b)*6ab = (a-b)³
(a-b)(2ab +(a+b)² - 6ab) = (a-b)³
(a-b)(2ab +a²+2ab +b² -6ab) = (a-b)³
(a-b)(a²-2ab +b²) = (a-b)³
(a-b)(a-b)² = (a-b)³
(a-b)³ ≡ (a-b)³
Похожие вопросы
Предмет: Геометрия,
автор: nassssssssstya
Предмет: Русский язык,
автор: MoNuN
Предмет: Українська мова,
автор: 123a34689
Предмет: Геометрия,
автор: meri333
Предмет: Математика,
автор: chieriepienin20